2016
DOI: 10.1107/s1600576715022621
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature powder X-ray diffraction measurements in vacuum: analysis of the thermal displacement of copper

Abstract: A serious limitation of the all‐in‐vacuum diffractometer reported by Straasø, Dippel, Becker & Als‐Nielsen [J. Synchrotron Rad. (2014), 21, 119–126] has so far been the inability to cool samples to near‐cryogenic temperatures during measurement. The problem is solved by placing the sample in a jet of helium gas cooled by liquid nitrogen. The resulting temperature change is quantified by determining the change in unit‐cell parameter and atomic displacement parameter of copper. The cooling proved successful, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The increase in the 100 K model is similar to what is observed in diamond (Wahlberg, Bindzus, Bjerg et al, 2016). Besides the mentioned studies on diamond and silicon, the EDD of cubic boron nitride (cBN) and copper have also been studied with AVID (Wahlberg et al, 2015;Wahlberg, Bindzus, Christensen et al, 2016). For cBN, it was possible to determine the deformation of the core EDD, even without the use of Wilson plots, which can only be rigorously used for monoatomic solids.…”
Section: Electron Density Modelling and Core Deformationmentioning
confidence: 56%
See 2 more Smart Citations
“…The increase in the 100 K model is similar to what is observed in diamond (Wahlberg, Bindzus, Bjerg et al, 2016). Besides the mentioned studies on diamond and silicon, the EDD of cubic boron nitride (cBN) and copper have also been studied with AVID (Wahlberg et al, 2015;Wahlberg, Bindzus, Christensen et al, 2016). For cBN, it was possible to determine the deformation of the core EDD, even without the use of Wilson plots, which can only be rigorously used for monoatomic solids.…”
Section: Electron Density Modelling and Core Deformationmentioning
confidence: 56%
“…Recently, the first version of the AVID was reported (Straasø et al, 2013(Straasø et al, , 2014. By performing PXRD in vacuum, the external background signal can, in the absence of fluorescence, be limited to (i) scattering from the sample container, which can be measured individually and subtracted, (ii) Compton scattering from the sample, and (iii) thermal diffuse scattering, which can be minimized by carrying out data collection at low temperature (Wahlberg, Bindzus, Christensen et al, 2016). The diffractometer had a sample-todetector distance of 300 mm (Straasø et al, 2013) and used a Fuji BAS SR-2040 imaging-plate (IP) detector positioned on a cylindrical path at the given distance.…”
Section: Diffraction In Vacuummentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the charge density studies from ultra-high resolution synchrotron radiation powder diffractions have been reported using an all-in-vacuum diffractometer installed at PETRA-III26. Core electron deformations of diamond26, silicon27 and cubic boron nitride28, and anharmonic thermal vibration of copper29 have been observed from powder diffraction data. Several analytical procedures such as Wilson plot26272829, and uncertainty estimation using particle statics27 were used in the studies.…”
mentioning
confidence: 99%
“…Core electron deformations of diamond26, silicon27 and cubic boron nitride28, and anharmonic thermal vibration of copper29 have been observed from powder diffraction data. Several analytical procedures such as Wilson plot26272829, and uncertainty estimation using particle statics27 were used in the studies. These techniques are under development since it still depends on materials262728.…”
mentioning
confidence: 99%